Calories versus protein in onset of renal disease in NZB x NZW mice. - Johnson, B C (1986)
Autoimmunity-prone (NZB x NZW)F1 (B/W) female mice are used as a model of human lupus erythematosus. When full-fed, these mice die of glomerulonephritis between 7 and 11 (average 9) months of age. When food intake is restricted to 60% of calories, the onset of this disease is delayed and the mice live greatly prolonged lives free of disease. Since high protein intake is commonly associated with acceleration of kidney damage in humans and experimental animals, the current experiments were designed to employ diets in which protein concentration was as high as possible. The observations demonstrate clearly that with this model of autoimmune disease, total calorie intake (from whatever source) exerts an overriding influence on life span. A higher calorie intake leads to early death and restricted-calorie intake leads to an increased life span. When B/W mice are full-fed, with respect to calories, feeding diets of greatly differing protein composition did not influence life span significantly. By contrast, calorie restriction of diets, even of very high protein content or of lower protein content, greatly prolonged life of B/W mice. Even with exceedingly high protein intake (greater than 83% of the calories) it is not protein per se but the total calorie intake that exerts the greatest influence that determines length of life in mice of this autoimmunity- and glomerulonephritis-prone strain.